Strengthening Data Security Systems in the Cyber Notary to Ensure Legal Certainty - Alisya Rahma Saebani (Yayasan Cerdas Pedia Indonesia, 2026)
The implementation of cyber notary practices in Indonesia currently encounters profound regulatory fragmentation among the Law on Notary Public Office, Electronic Information and Transactions Law, and Personal Data Protection Law. This fundamental normative vacuum triggers significant legal uncertainty in securing clients' electronic data. This normative legal research aims to comprehensively analyze the interconnection of positive legal instruments regarding privacy protection within the digital notarial ecosystem. Utilizing statutory, conceptual, and comparative approaches, this study critically evaluates the obligations of notaries who now transform into personal data controllers bearing absolute liability. The research findings demonstrate that the absence of uniform information security standards substantially elevates the risks of system hacking and digital identity breaches. Therefore, this research concludes the urgency for regulatory harmonization that strictly mandates the implementation of privacy by design principles alongside the standardization of encrypted information security systems. This legal measure constitutes an imperative directive to mitigate cybercrime threats.